PERANCANGAN SISTEM PENJADWALAN SEMINAR PROPOSAL BERBASIS WEB DI JURUSAN TEKNIK SIPIL POLITEKNIK NEGERI JAKARTA MENGGUNAKAN FRAMEWORK CODEIGNITER - Alif Nurrizki Pangestu; Kussigit Santosa (Politeknik Negeri Jakarta, 2021)
Scheduling seminar proposals at the Department of Civil Engineering, Politeknik Negeri Jakarta, the system currently used is manually using Microsoft Excel software, so the possibility of conflicts and delays in the preparation of the Proposal Seminar Schedule are often experienced. In this study, a web-based proposal seminar scheduling application with the name PSPTS will be designed to make it easier for students to submit files without having to go to campus, department administrations do not have to type data manually, and the head of the study program can arrange schedules online. Using Waterfall as the method, PHP (Hypertext Preprocessor) for the programming language base, Codeigniter for the framework and for data storage using MySQL. With the existence of a website with the name PSPTS, it can improve the quality and service at the Department of Civil Engineering at Politeknik Negeri Jakarta. Keywords : Scheduling, Proposal Seminars, Codeigniter, Waterfall.